FEEDING PRACTICES AND NUTRITIONAL STATUS IN CHILDREN OF ONE MONTH TO THREE YEARS OF AGE PRESENTING WITH ACUTE GASTROENTERITIS - Syed Sajid Hussain Shah; Shahzad Haider; Sajid Nazir (Journal of University Medical & Dental College, 2016)
ABSTRACTBACKGROUND: Acute Gastroenteritis (AGE) is the leading cause of death in third world countries. Feeding practices, water source and malnutrition are the well recognized risk factors for gastroenteritis. OBJECTIVE: This study had been conducted to ﬁnd out the feeding practices and nutritional status in children below three years of age among the community presenting with acute gastroenteritis. DESIGN: Observational study.METHODS: This study was carried out in the Department of Paediatirics, Pakistan Ordnance Factories (POF) Hospital Wah Cantt from January 2009 to August 2009. All the patients between the ages of one month to three years who were admitted in Paediatric ward of POF Hospital were included in the study. Patients were clerked on a pre-designed proforma.RESULTS: In our study 63% affected children were males and 37% were females. 32% children were exclusively breast fed. 42% males were Failure to thrive and 40% females were failure to thrive. As a whole most affected group was seven to twelve months old as this was 34%.CONCLUSION: AGE presents more in population less than two years of age, in whom breast thfeeding not giv en with no sex propensity. About 42% patients were failure to thrive (<5 centile weight for age).